IMPRISONMENT AID: ANALYSIS OF THE LEGAL ASPECTS OF SOCIAL SECURITY BENEFIT (Revista Direito em Debate, 2021)
The reclusion allowance is due to family members who are dependent on the Social Security insured who are in prison. In order to receive the benefit, the insured person must be contributing to the INSS for at least 24 months and meet several other requirements, which makes the benefit inaccessible to many policyholders, making only just over 8% of the prison population able to receive it. This study has a qualitative approach and is bibliographic-legal-theoretical. It is based especially on Law nº 8.213 / 91 which provides for Social Security benefit plans. The general objective of this paper is to analyze the social security legislation, more precisely with regard to Law nº 8.213 / 91, demonstrating its impacts on Brazilian society, and also the changes brought by MP 871/2019. And its specific objectives are to describe the importance of prison aid to society, identify the technical aspects by conducting a survey of the amounts that are paid, and present the legislative changes that have happened over the years. Questioning what is the social importance of imprisonment assistance for Brazilian society? In the end, it is considered that this benefit is necessary so that many families are not left helpless, allowing the principle of human dignity and the principle of individualization of the penalty to be respected as provided for in the Federal Constitution of 1988.
Keywords: Law 8.213/91. MP 871/2019. Social Security. Constitutional right. Termination of Benefit.